Analytical techniques in forensic science - Wolstenholme, Rosalind; Jickells, Sue; Forbes, Shari, 1977- (Hoboken, NJ : Wiley, 2020)
"Forensic science is typically defined as the application of science to the law; both criminal and civil law. Most people tend to associate forensic science with investigation of crimes such as burglary; arson; possession of illegal drugs; drug trafficking; drink and drug driving offences; attacks against the person including murder and sexual assault. However, forensic science is applied to investigation of a far wider range of potential prosecutions including war crimes; fraud; medical incidents; doping offences in sport; environmental pollution incidents; road traffic accidents; maritime and aviation incidents; industrial incidents; and issues relating to food authenticity"--
Includes bibliographical references and index.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: Forensic sciences -- Technological innovations; Electrochemical analysis; Electrochemistry